Breach of sensory integration in children and youth - Radziyevska Mariya; Dziągwa Ewelina; Radziyevsky Pawel (Kharkov National Pedagogical University, 2012)
From the first moments of life, the child acquires the experience of being in the world around him through the senses such as touch, balance, proprioception, taste, sight, hearing and smell. The development of sensory integration of individual processes helps to effectively carry out every activity and function in society. Changes in the quality and quantity of sensory information may lead to sensory integration disorder child, which is immediately reflected in his behavior. In this paper we have presented information on the levels of sensory integration and testing of samples with a simple touch of activities that can be done without special equipment, both at home and in child care. Dissemination of knowledge about the processes of sensory integration, both among doctors, teachers, physiotherapists, occupational therapists and psychology as well as parents can contribute to early diagnosis of problems in children sensory-social development, further impeding the normal functioning of the child in society.